Equilibrium of ensemble of ions, produced in plasma placed in crossed fields with positive radial electric field - Yeliseyev, Yu.N. (Вопросы атомной науки и техники, 2017)
The equilibrium of ensemble of ions produced in crossed fields with positive (directed outward) radial electric field is studied. The equilibrium ion distribution function and its moments – an ion density and hydrodynamic rotation frequency – are determined. Рассматривается равновесие ансамбля ионов, образовавшихся в скрещённых полях в положительном (направленном наружу) радиальном электрическом поле. Определена равновесная функция распределения ионов и её моменты – распределение плотности ионов и гидродинамическая частота вращения. Розглядається рівновага ансамблю іонів, що утворилися в схрещених полях у позитивному (спрямованому назовні) радіальному електричному полі. Визначена рівноважна функція розподілу іонів і її моменти – розподіл густини іонів і гідродинамічна частота обертання.